Corrosion at the carbon steel-clay borehole water interface under anoxic alkaline and fluctuating temperature conditions. (15th May 2018) - Schlegel, Michel L.; Necib, Sophia; Daumas, Sylvie; Labat, Marc; Blanc, Cécile; Foy, Eddy; Linard, Yannick
Highlights: Carbon steel coupons were corroded at 85 °C only or with room temperature transients. Damage was minimal at 85 °C only (<1 μm after 9 months). Minimal damage is related to a thin uniform layer of protective Fe-silicate. Damage was larger (38 μm after 2 years) when room temperature episodes occurred. Corrosion interface was separated in cathodic surfaces and anodic crevices. Abstract: Coupons of carbon steel were corroded in situ in anoxic clay porewater under slightly alkaline conditions. Sample damage was less than 1 μm for 9 months at 85 °C only, and corrosion interfaces were covered by a thin, protective layer of Fe-silicate. The damage was more significant for samples exposed to room temperature transients (up to 38 μm for two years), and the long-term surface differentiated in cathodic (Fe-silicate covered) areas and anodic crevices filled with siderite, chukanovite, β-Fe2 (OH)3 Cl, and covered by tubercles. Sulfide compounds were detected, and were related to the metabolism of sulfate-reducing prokaryotes detected by microbiological techniques.